Evaluasi Faktor-Faktor Penerimaan Quick Response Indonesia Standard (Qris) di Masyarakat Jabodetabek dengan Modifikasi Utaut 2 - Saputra, Deni; Lastiati, Anies (BUDGETING : Journal of Business, Management and Accounting, 2024)
The digital revolution has become a major driver of global economic change, accelerating the transformation of various sectors, including payment systems. In Indonesia, one of the important innovations that has emerged is the Quick Response Indonesia Standard (QRIS). This research is expected to provide in-depth insight into the factors that influence QRIS acceptance in the Jabodetabek area. This research is quantitative research. Data was obtained by distributing questionnaires via Google Form to 123 respondents. The data collected was then processed using SEM-PLS analysis. The results of this research explain that performance expectancy has a positive and significant influence on intention to use QRIS. On the other hand, effort expectancy and trust are not significant in influencing intention to use. Social influence and facilitating conditions are negatively and significantly related to intention to use, hedonic motivation and perceived security do not significantly influence intention to use QRIS. Price value shows a positive and significant influence, Habit has a positive and significant influence. Lastly, perceived risk has a negative and significant relationship, where perceived risk reduces the intention to use QRIS. Keywords: Facilitating Condition, Behavioral Intention, Performance Expectancy, Social Influence